Pemberdayaan Perempuan di Gampong Cot Girek Kota Lhokseumawe: Pengabdian Masyarakat - Ti Aisyah; Muhammad Hasyem; Nur Hafni; Ferizaldi; Mauludi; Murniati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Empowerment of village communities, including women's empowerment, requires important attention from the village government to free them from their helplessness, they need to be empowered to increase their power, abilities so that they are able to take advantage of access to opportunities in the community in meeting their needs and welfare. The Cot Girek Village Government, Lhokseumawe City has implemented an empowerment policy with several types of activity programs, namely empowerment in the fields of agriculture, animal husbandry and women's empowerment with funding sources from the Village Revenue and Expenditure Budget (APBG). Specifically the results of women's empowerment. The women's empowerment activity program is focused on the management of the Bakry Bread Industry MSME, the Bakry Bread industry business has been running since 2019, and during the Covid-19 period, the business was inactive, and after Covid the village government provided capital assistance again and motivated, so that the Bakry Bread MSME managed by women in the Cot Girek village is running smoothly again, production can meet the needs of customers around the village and is supplied to dayah and to stalls. The development of Roti Bakry MSME is still limited both in terms of production volume, facilities and marketing are still traditional and have not utilized digital technology (new media) in expanding marketing.